Assessment of competitiveness of industries in Kazakhstan and Russia - Stesenko, I.P.; Tasmaganbetov, A.B.; Aldashova, G.M. (BUKETOV BUSINESS REVIEW, 2019)
In the article the genesis and the potential of the Kazakh and Russian economic industrial cooperation are analyzed, as well as limiting factors and perspectives of its further development. In the article the dialectical relationship and the dualistic nature of cooperation and competitiveness are revealed. The authors’ hypothesis is based on the idea that the dominant purpose of industrial cooperation is a model of the active participation of the consolidated group of countries in the region eliminating the possibility of a drift towards the periphery. The authors used the concepts of methodological possibilities of the «theory of the new regionalism», «competitiveness theory» and geopolitical doctrine of Eurasianism tried to explain the background and development of the industrial capacity of the Kazakh and Russian economic cooperation, that allow to evaluate the quantitative and qualitative parameters of the functioning of the Kazakh and Russian economic and industrial cooperation, its limiting factors and perspectives for its further development. Modern features and problems of economic cooperation of Kazakhstan and Russia on macro - and meso-levels are revealed and ways of their decision are offered. Comparative analysis of the level of economic development of the Republic of Kazakhstan and the Russian Federation are assessed. The specificity of the KazakhRussian cooperation in the industrial (fuel and energy, transport, industrial), trade and investment spheres is studied and the author's assessment of the prospects of their development is given.